A retrospective study of orthodontic treatment on anterior tooth displacement caused by periodontal disease. Issue 13 (2nd April 2021) - Huang, Yi-zhi; Zhu, Yan-ru; Yan, Ying
Abstract : Abstract: This retrospective study aimed to explore the effect of orthodontic treatment (ODT) on anterior tooth displacement (ATD) caused by periodontal disease (PD). A total of 72 patients were selected and were divided into a control group (n = 36) and an experimental group (n = 36). Patients in both groups received conventional periodontal treatment. In addition, patients in the experimental group also received ODT. Outcomes include probing depth, percentage of bleeding sites, clinical attachment loss, clinical crown length, tooth root length, and periodontal tissue of the affected tooth (alveolar bone height, periodontal pocket depth, bleeding index). After treatment, the patients in the experimental group achieved more improvements in probing depth ( P  < .01), percentage of bleeding sites ( P  < .01), clinical attachment loss ( P  < .01), clinical crown length ( P  = .04), and periodontal tissue of the affected tooth (periodontal pocket depth ( P  < .01), and bleeding index ( P  < .01)), than those of patients in the control group. This study suggests that ODT is beneficial for ATD caused by PD. Future studies are still needed to verify the findings of this study.